(untitled) (Journal of Management and Social Sciences, 2022)
The study examines the effect of poverty and unemployment on economic growth in selected sub-Saharan Africa (SSA) covering the period 1991 to 2018. The study employs Panel OLS regression analysis technique using the fixed effect model to establish the impact of poverty and unemployment on the economic growth in SSA. The study also examines long-run relationship among the variables using the Vector Error Correction Model (VECM) framework. The study finds that poverty (measured as per capita income) had a positive and significant effect on economic growth in the region while unemployment had a negative and insignificant effect on economic growth within the study period. The study also finds that there exists a long-run relationship among poverty, unemployment and economic growth in SSA. The study concludes that an increase in per capita income (i.e. reduction in poverty level) enhances economic growth in the region. The study recommends that there should be further improvement in per capita income (as a measure of poverty) in order to transform economic activities in the countries. Also, the government should fully engage unemployed people in productive activities which in turn accelerate the economic growth of the selected countries. Keywords: Poverty; Unemployment; Economic Growth; sub-Saharan Africa